2015
DOI: 10.1039/c5ra17376k
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating ordered silicon carbide nanorods by preceramic polymer nanocasting

Abstract: Top: Schematic representation of the hard templating approach. Bottom left: SAXS profiles at each step of the SiC elaboration. Bottom right: SEM images of porous SiC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Templating approaches appear as promising processes in order to control SiC porosity with typical pore diameters lower than 50 nm. It has been shown that mesopororous silica can be considered as hard templates resulting in rod-like SiC, showing high specific surface area [8,9]. Likewise, polycarbosilane (PCS) infiltration method with silica nanofoam as template led to synthesis of SiC nanofoams with a controlled porosity and pore size ranging between 10 and 100 nm [10].…”
Section: Introductionmentioning
confidence: 99%
“…Templating approaches appear as promising processes in order to control SiC porosity with typical pore diameters lower than 50 nm. It has been shown that mesopororous silica can be considered as hard templates resulting in rod-like SiC, showing high specific surface area [8,9]. Likewise, polycarbosilane (PCS) infiltration method with silica nanofoam as template led to synthesis of SiC nanofoams with a controlled porosity and pore size ranging between 10 and 100 nm [10].…”
Section: Introductionmentioning
confidence: 99%
“…As the other nanostructures, the por-SiC can be obtained by a “bottom-up” approach, which includes the formation of the por-SiC structure from low-molecular substances, as well as a “top-down” approach, through porosification of bulk SiC . Reactions used for the “bottom-up” synthesis of the por-SiC include carbothermal , or magnesiothermal , reduction of C/SiO 2 nanocomposites and interaction of porous carbon with silicon monoxide , or silicon powder. ,, Significant attention was paid to a nanocasting method based on the thermal decomposition of special preceramic polymer (polycarbosilane) confined inside the pores of solid SiO 2 template, assembled around semifluorinated alkane molecular template or included as a polycarbosilane unit into the block copolymer. , However, the por-SiC obtained by carbothermal reduction or by reaction with SiO commonly demonstrates low surface area, disordered porous morphology, and wide pore size distribution due to the vapor-phase reaction mechanisms . The nanocasting-derived por-SiC with well-defined morphology is rather semiamorphous than crystalline material.…”
Section: Introductionmentioning
confidence: 99%